PERSEPSI PETANI TERHADAP PENGGUNAAN PADI VARIETAS UNGGUL DI DESA SUNGAI KAKAP KECAMATAN SUNGAI KAKAP - Youlla, Donna; Firmana, Heky (Jurnal Ekonomi STIEP, 2022)
The research aimed to assess farmers' perceptions of using superior rice varieties in Sungai Kakap Village, Sungai Kakap District, Kubu Raya Regency, conducted from June to August 2021. It employed qualitative descriptive methods, gathering primary data through field observations and interviews with Extension Workers and Farmers, supplemented by secondary data from relevant documents. The study population comprised 300 farmers, with a sample size of 30 respondents chosen through Simple Random Sampling. Variables examined included age, education level, farming experience, land area, and rice production level, alongside Farmers' Perceptions guided by Jalali's indicators. Data analysis utilized Average Score with Likert Scale. Results indicated that farmers' perceptions scored an average of 3.09, indicating a Good rating overall. Among perceptions, the ease of obtaining superior rice seeds scored lowest at 3.57, still falling within the Good rating. Conversely, Farmers' Perception of the Quality of Superior Rice Production scored highest at 4.47, indicating Very Good. Thus, the study concluded that farmers generally held positive perceptions of using superior rice varieties in Sungai Kakap Village, Sungai Kakap District, Kubu Raya Regency, with particular satisfaction regarding the quality of the rice produced.